Three essays in feminist economics: empirical & historical applications - Small, Sarah F., author; Braunstein, Elissa, advisor; Pena, Anita Alves, committee member; Weiler, Stephan, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2022)
This dissertation includes three essays in feminist economics. The first two are quantitative empirical studies, which study the interactions between paid work, allocations of housework, and intrahousehold power dynamics. Chapter 1 examines the extent to which men extract unpaid household labor from women to support entrepreneurial ventures. Models using Panel Study of Income Dynamics (PSID) data from 1985 to 2019 illustrate that, in married White couples, women's disproportionate share of housework increases when their husbands take on business ownership. However, there is no evidence that White husbands extend such support when their wives own businesses. In Black couples, wives take on even greater housework shares when they own a business. These dynamics suggest that the success of married White men's entrepreneurship may be built on extracting domestic labor from their wives: a notion consistent with patriarchal rent seeking theories. Chapter 2 offers a quantitative test of hegemonic masculinity theory and demonstrates how men of different race and income groups respond to their women partners out-earning them— an economic 'threat' to masculinity. Results indicate in upper-income White men have a strong aversion to the situation in which a woman out-earns her male partner. As hegemonic masculinity theory would suggest, middle-income White men follow suit, but lower income White men, and Black men in most income groups, do not. The third chapter is a qualitative history of Barbara Bergmann's occupational crowding hypothesis. The chapter situates the hypothesis among contemporary competing theories on the economics of discrimination and explains why the crowding hypothesis did not persist as a major explanation of wage differences in the mainstream of the economics profession. Each chapter contributes to the feminist economic mission to overcome androcentric bias in economic analysis, to speak to power, and to extinguish oppression.
Keywords: feminist economics; history of economic thought; entrepreneurship; occupational crowding hypothesis; hegemonic masculinity